Changes in soil moisture drive soil methane uptake along a fire regeneration chronosequence in a eucalypt forest landscape. (23rd September 2015) - Fest, Benedikt; Wardlaw, Tim; Livesley, Stephen J.; Duff, Thomas J.; Arndt, Stefan K.
Abstract Disturbance associated with severe wildfires (WF) and WF simulating harvest operations can potentially alter soil methane (CH4) oxidation in well‐aerated forest soils due to the effect on soil properties linked to diffusivity, methanotrophic activity or changes in methanotrophic bacterial community structure. However, changes in soil CH4 flux related to such disturbances are still rarely studied even though WF frequency is predicted to increase as a consequence of global climate change. We measured in‐situ soil–atmosphere CH4 exchange along a wet sclerophyll eucalypt forest regeneration chronosequence in Tasmania, Australia, where the time since the last severe fire or harvesting disturbance ranged from 9 to >200 years. On all sampling occasions, mean CH4 uptake increased from most recently disturbed sites (9 year) to sites at stand 'maturity' (44 and 76 years). In stands >76 years since disturbance, we observed a decrease in soil CH4 uptake. A similar age dependency of potential CH4 oxidation for three soil layers (0.0–0.05, 0.05–0.10, 0.10–0.15 m) could be observed on incubated soils under controlled laboratory conditions. The differences in soil CH4 uptake between forest stands of different age were predominantly driven by differences in soil moisture status, which affected the diffusion of atmospheric CH4 into the soil. The observed soil moisture pattern was likely driven by changes in interception or evapotranspiration with forest age, which have been well described for similar eucalypt forest systems in south‐eastern Australia. Our results imply that there is a large amount of variability in CH4 uptake at a landscape scale that can be attributed to stand age and soil moisture differences. An increase in severe WF frequency in response to climate change could potentially increase overall forest soil CH4 sinks.